Sharia Social Capital Construction in Strengthening the Community Economy by National Zakat Agency Institutions Yatim Mandiri Surabaya - Yazid, Muhammad; Prasetyo, Aji (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research was conducted to analyze the social capital construct that can strengthen the community's economy as carried out by the Yatim Mandiri Surabaya Amil Zakat Institution (LAZ). This research method uses descriptive qualitative with data obtained using interview techniques. The data obtained was analyzed through the stages of data reduction, data display, and conclusion. The results of the research show the construct of social capital at the National Amil Zakat Institution (LAZ) Yatim Mandiri Surabaya, namely in the form of providing capital in the form of education and training as well as business funds for orphans in the Mandiri Entrepreneur Center (MEC) program and poor mothers in the Bunda program. Mandiri Sejahtera (BISA). The social capital construct at LAZ Yatim Mandiri Surabaya in strengthening the community's economy is specifically for groups of poor orphan mothers in the Kampung Mandiri program. This program is an empowerment program in the village/village/region area to optimize village potential through the intervention of forming joint business groups. Through this program, the community can implement the social capital construct in the form of cooperation in managing funds from LAZ Yatim Mandiri Surabaya for a joint venture. The ultimate goal of providing and fostering social capital by LAZ Nasional Yatim Mandiri Surabaya is so that orphans and their mothers can live independently and be economically strong.